2016
DOI: 10.1002/ajh.24561
|View full text |Cite
|
Sign up to set email alerts
|

Iron refractory iron deficiency anemia: a heterogeneous disease that is not always iron refractory

Abstract: TMPRSS6 variants that affect protein function result in impaired matriptase-2 function and consequently uninhibited hepcidin production, leading to iron refractory iron deficiency anemia (IRIDA). This disease is characterized by microcytic, hypochromic anemia and serum hepcidin values that are inappropriately high for body iron levels. Much is still unknown about its pathophysiology, genotype-phenotype correlation, and optimal clinical management. We describe 14 different TMPRSS6 variants, of which 9 are novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 46 publications
3
48
0
Order By: Relevance
“…A spectrum of conditions can be envisaged ranging from classic severe IRIDA due to homozygous or compound heterozygous TMPRSS6 mutations to increased susceptibility to iron deficiency conferred by single mutations/polymorphic changes. One approach proposed to predict classic IRIDA is hepcidin normalization on other iron parameters, as ratios transferrin saturation (Tsat)/log hepcidin or Tsat/log Ferritin (Donker et al, 2016). According to other authors, most patients with a severe IRIDA phenotype have biallelic TMPRSS6 mutations and, when unidentified, the second allele may be genetically occult (Heeney et al, 2018).…”
Section: Anemias With Abnormal Hepcidin Levelsmentioning
confidence: 99%
“…A spectrum of conditions can be envisaged ranging from classic severe IRIDA due to homozygous or compound heterozygous TMPRSS6 mutations to increased susceptibility to iron deficiency conferred by single mutations/polymorphic changes. One approach proposed to predict classic IRIDA is hepcidin normalization on other iron parameters, as ratios transferrin saturation (Tsat)/log hepcidin or Tsat/log Ferritin (Donker et al, 2016). According to other authors, most patients with a severe IRIDA phenotype have biallelic TMPRSS6 mutations and, when unidentified, the second allele may be genetically occult (Heeney et al, 2018).…”
Section: Anemias With Abnormal Hepcidin Levelsmentioning
confidence: 99%
“…Examples include (a) evaluation of suspected IRIDA 5,6,8 ; (b) diagnosis of concomitant ID in patients with anemia of inflammation 9 ; (c) prediction of responsiveness to oral iron therapy and guiding iron treatment under conditions of competing signals (anemia, ID, inflammation) [10][11][12] ;…”
Section: Introductionmentioning
confidence: 99%
“…However, GWAS are needed in a large sample of our population to identify and define the frequency of TMPRSS6 and other iron‐related gene polymorphisms. Moreover, queries arising from our study, such as why all of the cases affected with genetic variations are male in present study, although a recent report has shown that more females were affected in an IRIDA cohort (Donker et al , ), needs to be investigated in larger prospective studies. Do other genetic factors related with ethnicity in our region affect iron‐related genes or are some trans‐acting genes or factor(s) on the X‐chromosome responsible for this phenotype?…”
Section: Discussionmentioning
confidence: 80%